Intimate partner violence and its association with skilled birth attendance among women in Nigeria: evidence from the Nigeria Demographic and Health Surveys - Chukwuechefulam Kingsley Imo; Nnebechukwu Henry Ugwu; Ukoji Vitalis Ukoji; Uche Charlie Isiugo-Abanihe (BMC, 2022)
Abstract Background Intimate Partner Violence (IPV) has been identified as a violation of human rights and a major public health challenge. IPV against women has negative effects on women's mental well-being and leads to unfavourable health outcomes through poor maternal healthcare services utilisation, especially skilled birth attendance (SBA). This study examined the trends in IPV and SBA, as well as the different forms of IPV as predictors of SBA in Nigeria. Methods Data for the study were derived from a nationally representative weighted sample of 34,294 women selected and interviewed for the questions on the domestic violence module in the three consecutive Nigeria Demographic and Health Surveys conducted in 2008, 2013 and 2018. Descriptive and analytical analyses were carried out, including frequency distribution and binary logistic regression model at the multivariate level. The results of the explanatory variables were expressed as odds ratio (OR) and 95% confidence intervals (CI). Results The prevalence of emotional and physical IPV among the sampled women decreased in 2013 from 2008 but later increased in 2018. Sexual IPV increased from 4.1% in 2008 to 7.6% in 2018, while births delivered with the assistance of skilled providers increased from 37.7% in 2008 to 50.8% in 2018. The likelihood of using SBA significantly decreased among women who experienced emotional IPV in 2008 (aOR: 0.74; CI: 0.63-0.87) and sexual IPV in 2018 (aOR: 0.62; CI: 0.45-0.86). Women who experienced physical IPV were more likely to use SBA in 2008, 2013 and 2018 (aOR: 1.72; CI: 1.55-1.92; aOR: 1.40; CI: 1.26-1.56 and aOR: 1.33; CI: 1.15-1.54, respectively). The covariates have varying degrees of influence on SBA across the survey years. Conclusions The showed that the prevalence of emotional and physical IPV increased in 2018 after a decrease in 2013, with an increase in sexual IPV and the use of SBA across the survey years. Also, emotional and sexual IPV, unlike physical IPV are associated with low chances of using SBA. There is a need for more pragmatic intervention programmes towards eliminating all forms of violence against all women, reducing maternal and child mortality and promoting the empowerment of women.